(untitled) (Bangladesh Journal of Medicine, 2013)
Background: Accelerated decline of bone mass occurs in women after the menopause, and might lead to excessive bone resorption and eventually to osteoporosis. To find out the changes of bone mineral density (BMD) before and after menopause, the shown was undertaken. Materials and Methods: This comparative study was conducted in the Department of Medicine, Sylhet M A G Osmani Medical College Hospital, Sylhet during July 2008 to June 2009. Forty postmenopausal women; monthly income and BMI matched 40 premenopausal women were selected according to inclusion and exclusion criteria. BMD of lumber vertebrae and femoral neck was determined using Dual energy x-ray absorptiometry (DXA) method (Norland XR 46, Pencil beam). Results: The parity of the postmenopausal women was significantly higher than that of premenopausal women (6.9 ± 2.6 vs 3.1± 1.5; p<0.01). The body weight was significantly lower in postmenopausal women than that of premenopausal women (54.1 ± 8.3 kg vs 61.0 ± 9.7 Kg; p<0.01). The height was significantly lower in postmenopausal women than premenopausal women (148.2 ± 5.7cm vs 153.4 ± 6.4cm; p<0.01). The BMD was lower in postmenopausal women than premenopausal women in lumber vertebrae (0.68 ± 0.13 gm/cm2 vs 0.94 ± 0.03 gm/cm2; p <0.01) and also in femoral neck (0.63 ± 0.12 gm/cm2 vs 0.84 ± 0.14 gm/cm2; p < 0.01). A significant positive correlation was present between BMD and height (r=0.512; p<0.05); and weight (r=0.489; p<0.05); and a negative correlation between BMD and age (r=-0.408; p<0.05); parity (r=-0.456; p<0.05) and years since menopause (r=-0.350; p<0.05). Conclusion: The BMD was significantly lower in postmenopausal women than that of premenopausal women and negative correlation was present between BMD and age, parity and years since menopause. DOI: http://dx.doi.org/10.3329/bjmed.v22i1.13592 Bangladesh J Medicine 2011; 22: 1-7